Atividade de vocalização de Crossodactylus schmidti (Anura: hylodidae) sob a influência da radiação ultravioleta - Mainardi, Álvaro Augusto (2020)
Anthropogenic activities, such as the release of polluting gases and deforestation, accelerate the stratospheric ozone depletion increasing the incidence of ultraviolet radiation (UVR). Even though essential for life, UVR has negative effects on human health, biodiversity, and economy. This makes the measurement of UVR doses essential for both economic decisions and for the conservation of groups such as amphibians, which are sensitive to environmental changes. Therefore, the present work is divided into two sections: the development of an equipment capable of measuring solar ultraviolet radiation doses in natural environments, and its use to verify the influence of ultraviolet radiation on the calling behavior of Crossodactylus schmidti. The developed equipment is managed by a microcontroller and has a set of sensors capable of registering the ultraviolet radiation A, B, visible light, and air temperature. It is also independent of the electrical grid and does not require technical personnel for use. The use of this equipment has been tested and validated using others commercial types of equipment. To verify the influence of UVR on the studied species, we used the developed equipment to monitor the UVR doses and for recording the vocalization activity a recorder's array was used, being both installed at the species calling site. The results obtained in the first section of this work demonstrate that our equipment works very well and with high precision, and has the potential to reach various economic sectors such as agriculture, information technology services, scientific development, and human health care. The results obtained in the second part of this project show a negative effect of UVB on the mean duration of calls and on the probability of calling behavior, a positive effect of UVA on the mean duration of calls, as well as a positive effect of the abundance of co-specific males. Therefore, this work demonstrates that the development of new technologies applied to the continuous measurement of solar ultraviolet radiation is of great importance for human development and for the conservation of species.